The girl in the spider's web [videorecording (DVD)] - Alvarez, Fede, 1978-; Alvarez, Fede, 1978-; Foy, Claire, 1984-; Sverrir Gudnason, 1978-; Stanfield, LaKeith, 1991-; Lagercrantz, David (Sony Pictures Home Entertainment, 2019)
Lisbeth Salander and journalist Mikael Blomkvist work together to rescue a dangerous computer program from the hands of an evil figure from Lisbeth's past.